2022
DOI: 10.20417/nzjecol.47.3511
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of North Island kākā (Nestor meridionalis septentrionalis) within Pureora Forest Park, 2000–2020

Abstract: To test the long-term efficacy of mammalian pest control, annual distance sampling estimates of the density of North Island kākā (Nestor meridionalis septentrionalis) within the southern Waipapa Ecological Area (WEA), Pureora Forest Park from 2008-2020 are compared to previously published estimates made at the same sites and time of year (October) between 2000-2007. Kākā density increased approximately four-fold from an average of c. 0.5 (95% CI 0.5-0.6) birds ha −1 between 2000 and 2007 to c. 2.3 (95% CI 1.9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Mist-netting kākā has mostly been shown not to be gender selective and the sex ratio of birds caught can be used as an indicator of the status of a population (Greene & Fraser 1998;Wilson et al 1998). However, timing of capture can affect the sex ratio of birds caught (Greene & Fraser 1998).…”
Section: Catching and Radio Tagging Kākāmentioning
confidence: 99%
See 2 more Smart Citations
“…Mist-netting kākā has mostly been shown not to be gender selective and the sex ratio of birds caught can be used as an indicator of the status of a population (Greene & Fraser 1998;Wilson et al 1998). However, timing of capture can affect the sex ratio of birds caught (Greene & Fraser 1998).…”
Section: Catching and Radio Tagging Kākāmentioning
confidence: 99%
“…Mist-netting kākā has mostly been shown not to be gender selective and the sex ratio of birds caught can be used as an indicator of the status of a population (Greene & Fraser 1998;Wilson et al 1998). However, timing of capture can affect the sex ratio of birds caught (Greene & Fraser 1998). We explored the effect of timing of capture and predator control on the sex ratio of kākā we caught in mist nets using logistic generalised linear models (Appendix S1 in Supplementary Material).…”
Section: Catching and Radio Tagging Kākāmentioning
confidence: 99%
See 1 more Smart Citation
“…We aimed to assess risk exposure using range distributions and dynamic space use in a reintroduced parrot population in a fenced conservation reserve, and to highlight the utility of both approaches. Kākā ( Nestor meridionalis ) are large‐brained, social parrots (Bond & Diamond, 2004; Iwaniuk et al, 2005) that are considered generalist, extractive foragers (Beggs & Wilson, 1987; Moorhouse, 1997). These traits suggest a propensity for exploration and innovation (Dunbar & Shultz, 2007; Sol et al, 2005), which has been observed particularly in juvenile kākā (Bond & Diamond, 2004; Loepelt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to assess risk exposure using range distributions and dynamic space use in a reintroduced parrot population in a fenced conservation reserve, and to highlight the utility of both approaches. Kākā (Nestor meridionalis) are large-brained, social parrots (Bond & Diamond, 2004;Iwaniuk et al, 2005) that are considered generalist, extractive foragers (Beggs & Wilson, 1987;Moorhouse, 1997). These traits suggest a propensity for exploration and innovation (Dunbar & Shultz, 2007;Sol et al, 2005), which has been observed particularly in juvenile kākā (Bond & Diamond, 2004;Loepelt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%